Implementation of e-service quality by front office department in increasing guest satisfaction at Movenpick Resort & Spa Jimbaran Bali - Kadek Hindra Wijaya Putra; I Gusti Agung Mas Krisna Komala Sari; I Nyoman Winia (Journal of Applied Sciences in Travel and Hospitality, 2022)
This study was conducted to determine the implementation of e-service quality by the front office department to guest satisfaction and to determine the percentage of guest satisfaction with e-service quality by the front office department at Mevenpick Resort & Spa Jimbaran Bali. This study uses a qualitative descriptive analysis method. Data were obtained by means of observation, documentation and interviews with informants who were considered to understand the research problem, namely the implementation of e-service quality by the front office department and the percentage of guest satisfaction with e-service quality by the front office department at Mevenpick Resort & Spa Jimbaran Bali. Data collection methods used in this study were observation, documentation and interviews. The results of this study indicate that a total of 7 indicators (efficiency, reliability, compliance, privacy, responsiveness, compensation, contact) and a total of 21 sub-indicators of e-service quality have been fully implemented by the front office. staff at Movenpick Resort & Spa Jimbaran Bali. The implementation of e-service quality plays a very effective and efficient role in increasing guest satisfaction, as evidenced by the results of the percentage of guest satisfaction which has increased by 3.13% from before the implementation of e-service quality, which is 86.88%. Then after the implementation of e-service quality increased to 90.01%. Then it is known that of the 7 e-service quality indicators that have been implemented several indicators arere felt or considered by guests to be able to provide increased satisfaction during their stay, such as fulfillment, responsiveness, and contact.